2018
DOI: 10.1101/435818
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-lab EcoFAB study shows highly reproducible physiology and depletion of soil metabolites by a model grass

Abstract: There is a dynamic reciprocity between plants and their environment: On one hand, the physiochemical properties of soil influence plant morphology and metabolism, while on the other, root morphology and exudates shape the environment surrounding roots. Here, we investigate both of these aspects as well as the reproducibility of these responses across laboratories. The model grass Brachypodium distachyon was grown in phosphate-sufficient and phosphate-deficient mineral media, as well as in sterile soil extract,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…In this study, exudates were collected from roots with rhizosphere substrate still attached. The largest difference in this dataset was observed between soil-grown and sand- or clay-grown plants, which might be explained by soil-derived metabolites co-extracted with root exudates (Sasse et al, 2018; Miller et al, 2019). The authors showed some ions to be specifically up- or down-regulated in exudates of clay- vs. sand-grown plants, but their effect was not strong enough to separate the two conditions in a principal component analysis (Miller et al, 2019), which might be due to their exudate collection method, which was a mixture between the in situ and in vitro conditions utilized here.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In this study, exudates were collected from roots with rhizosphere substrate still attached. The largest difference in this dataset was observed between soil-grown and sand- or clay-grown plants, which might be explained by soil-derived metabolites co-extracted with root exudates (Sasse et al, 2018; Miller et al, 2019). The authors showed some ions to be specifically up- or down-regulated in exudates of clay- vs. sand-grown plants, but their effect was not strong enough to separate the two conditions in a principal component analysis (Miller et al, 2019), which might be due to their exudate collection method, which was a mixture between the in situ and in vitro conditions utilized here.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, changes in root morphology of plants grown in phosphate-limited clay might be distinct from plants grown in phosphate-limited sand or glass beads. Plants grown in soil may exhibit additional changes in root morphology and metabolism, as shown for B. distachyon grown in a sterile soil extract, which showed reduced root length, elongated root hairs, and depleted a variety of metabolites from soil extract (Sasse et al, 2018). Root systems further respond to local alterations in soil structure, such as to the presence of micro- or macropores, or to air pockets (Rellán-Álvarez et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of nutrient ions with efflux water would be undesirable. It is possible nutrients may be specifically resorbed by the root with other exuded metabolites (see Sasse et al, 2019).…”
Section: Figmentioning
confidence: 99%
“…This approach uses sigmoidal model fits to define the midpoint of substrate depletion from the media (t 50 ) and parse out substrate preferences during microbial growth. It has on October 31, 2020 by guest http://aem.asm.org/ Downloaded from been used in conjunction with both natural (37)(38)(39) and defined, complex medias (40) and shown the ability to link isolate exometabolite profiling with in situ community function (41).…”
Section: Introductionmentioning
confidence: 99%